2003
DOI: 10.1021/jp034345q
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Gold Nanoparticles by Femtosecond Laser Ablation in an Aqueous Solution of Cyclodextrins

Abstract: Gold nanoparticles were produced by femtosecond laser ablation of a gold metal plate in an aqueous solution of α-cyclodextrin (CD), β-CD, or γ-CD. The gold nanoparticles exhibited the UV−vis absorption spectrum with a maximum absorption band at 520 nm, similar to that of gold nanoparticles chemically prepared in a solution. The size distribution of the nanoparticles measured by transmission electron microscopy (TEM) shifted to a drastically smaller size of ∼2−2.4 nm and narrower size distribution of less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(158 citation statements)
references
References 26 publications
7
150
1
Order By: Relevance
“…32 For instance, due to the presence of some higher oxidation states at high pH, they can possess O − functionalization, making hydrogen bonding interactions possible. 29,32 Au-NPs can thus be noncovalently conjugated to oligosaccharides, 32,33 polymers, 34 proteins, 35 and oligonucleotides. 36 Such direct conjugation (without any group ligand-specific binding) promotes those Au-NPs as novel classes of biocompatible materials for various biological applications that have been underdeveloped or not fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…32 For instance, due to the presence of some higher oxidation states at high pH, they can possess O − functionalization, making hydrogen bonding interactions possible. 29,32 Au-NPs can thus be noncovalently conjugated to oligosaccharides, 32,33 polymers, 34 proteins, 35 and oligonucleotides. 36 Such direct conjugation (without any group ligand-specific binding) promotes those Au-NPs as novel classes of biocompatible materials for various biological applications that have been underdeveloped or not fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the size of gold NPs produced in water increases with increasing laser pulse energy [17]. The variation in pH of various solutions influences not only the NP size [13,18], but also the stability of gold colloids [19]. Despite numerous attempts to control the structural properties of gold NPs through synthesis parameters, a solid explanation of the influence of added chemicals on the size of gold NPs has not yet been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…We used relatively low laser fluences (1 J ⋅ cm 2 ) to avoid the phenomenon of laser-assisted plasma breakdown of the liquid, but the radiation intensity was high enough to ablate the suspended nanoparticles. As shown in previous studies, [32][33][34] when the pumping laser wavelength is relatively far from the absorption band of Au nanoparticles (depending on nanoparticle size), the nanoparticles are predominantly ablated by radiation from a white light supercontinuum (presenting a wide spectrum from ultraviolet [UV] to infrared of femtosecond pulse length), generated in the water environment due to nonlinear self-focusing effects that normally accompany femtosecond laser-liquid interaction. 37 In our experiments, this white light supercontinuum was clearly visible in the liquid volume.…”
Section: Synthesis Of Au Nanoparticlesmentioning
confidence: 88%
“…2,3 In addition, lasersynthesized nanoparticles can exhibit unique surface chemistry. In particular, due to a slight surface oxidation 31 gold nanoparticles can react not only with non-biocompatible surfactants (sodium dodecyl sulfate and cetyl trimethyl ammonium bromide), but also with OH groups of fully biocompatible substances such as cyclodextrins 32 or some polymers (eg, polyethylene glycol and dextran), 33 opening up new attractive pathways for biological applications. Surprisingly, despite the above-stated set of formidable properties, optical characteristics of laser-synthesized nanoparticles (except the absorption/scattering spectral feature associated with the excitation of plasmons) have not yet been systematically studied.…”
Section: Introductionmentioning
confidence: 99%